Multislice CT angiography in abdominal aortic aneurysm treated with endovascular stent grafts: evaluation of 2D and 3D visualisations - Sun, Zhonghua (University of Malaya, 2007)
Endovascular repair of abdominal aortic aneurysms has been introduced into the clinical practice for more than a decade and has been confirmed to be an effective alternative to conventional open surgery, especially in patients with co-morbid medical conditions. Helical CT angiography is the preferred imaging method in the follow-up of endovascular repair. Recent introduction of multislice CT scanners has augmented its diagnostic role in this area. Diagnostic value of multlislice CT has been complemented by a series of 3D postprocessings which assist vascular surgeons to accurately assess the effect of endovascular repair by providing additional information when compared to conventional 2D axial images. These reconstructions include multiplanar reformation, curved multiplanar reconstruction, shaded surface display, maximum intensity projection, volume rendering and virtual endoscopy. In this article, we aimed to demonstrate the generation of these 2D/3D reconstructions in based on multislice CT data acquired from a group of patients with abdominal aortic aneurysm following endovascular repair. A brief introduction of generating each reconstruction was provided; potential clinical applications of each reconstruction were briefly discussed. Images were presented in dynamic format with aim of allowing the reader to easily understand the postprocessing of these reconstructions.